2017
DOI: 10.1002/mus.25542
|View full text |Cite
|
Sign up to set email alerts
|

Vastus medialis and lateralis activity during voluntary and stimulated contractions

Abstract: These results can be explained by the relatively small contribution of the VM muscle to knee extension torque at short muscle length. Such disadvantage of the VM muscle at extended knee positions does not seem to be compensated by an increased neural drive. Muscle Nerve 56: 968-974, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
17
0
3
Order By: Relevance
“…Our results provide important insights about the functional interpretation of the covariation between quadriceps muscle activity. Although previous studies have demonstrated a strong correlation between the activity of VM and VL (10,(41)(42)(43), the functional role of this correlation has not been clear. Since VM and VL have the same contribution to task variables and produce opposing mediolateral patellar forces (11), their strong correlation is consistent with both simplification of task performance (16,19) and regulation of internal joint stresses (41,44,45).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results provide important insights about the functional interpretation of the covariation between quadriceps muscle activity. Although previous studies have demonstrated a strong correlation between the activity of VM and VL (10,(41)(42)(43), the functional role of this correlation has not been clear. Since VM and VL have the same contribution to task variables and produce opposing mediolateral patellar forces (11), their strong correlation is consistent with both simplification of task performance (16,19) and regulation of internal joint stresses (41,44,45).…”
Section: Discussionmentioning
confidence: 84%
“…This strategy might simplify task performance by reducing the number of variables that need to be specified for the production of behavior. For example, the quadriceps muscles VL and VM have very similar contributions to task performance with each muscle producing a similar extension torque at the knee (9)(10)(11); in rats, which have knees that can move in both flexion/extension and pronation/supination, VM and VL produce similar actions along all degrees of freedom (11). Consistent with the proposal that covariation patterns reflect muscles' contribution to task performance (7,(12)(13)(14)(15), the activations of VM and VL are strongly correlated (15)(16)(17)(18), suggesting that the CNS might control VM and VL as a single functional unit to simplify the achievement of task goals (19).…”
mentioning
confidence: 99%
“…Our results provide important insights about the functional interpretation of the co-variation between quadriceps muscle activity. Although previous studies have demonstrated a strong correlation between the activity of VM and VL [10,[29][30][31], the functional role of this correlation has not been clear. Since VM and VL have the same contribution to task variables and produce opposing mediolateral patellar forces [11], their strong correlation is consistent with both simplification of task performance [16,19] and regulation of internal joint stresses [29,32,33].…”
Section: Functional Role Of Muscle Co-variation In Quadricepsmentioning
confidence: 84%
“…This strategy might simplify task performance by reducing the number of variables that need to be specified for the production of behavior. For example, the quadriceps muscles vastus lateralis (VL) and vastus medialis (VM) have very similar contributions to task performance, with each muscle producing a similar extension torque at the knee [9][10][11]. Consistent with the proposal that co-variation patterns reflect muscles' contribution to task performance [7,[12][13][14][15], the activations of VM and VL are strongly correlated [15][16][17][18], suggesting that the CNS might control VM and VL as a single functional unit to simplify the achievement of task goals [19].…”
Section: Introductionmentioning
confidence: 99%
“…lateral para a medial do músculo, levando à maior magnitude de ativação (Murray et al, 2013;Visscher et al, 2017). Em uma linha mais antiga e contrária, outros grupos de investigação não reportam diferenças significativas (p < 0,05) na ativação elétrica do VL durante as condições de rotações dos pés (Alkner, Tesch & Berg, 2000;Signorile et al, 1995).…”
Section: Resultsunclassified